Studying vault board behavior: A preliminary look - Sands, A.; Smith, S. L.; Pacentini, T.
The purpose of this study was to provide some preliminary information on the vault board. These initial results are part of a much larger ongoing study of the behaviors of gymnastics apparatuses.